Sustainable health and long-term care solutions for an aging population - Fong, Ben, 1954-; Ng, Artie, 1966-; Yuen, Peter, 1953- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2018)
"This book explores the issues pertinent to health cost and ways of financing health care, development of innovative service models to meet the increased demands, designing infrastructure of collection and utilization of data for performance and quality improvement, and setting the framework for training and research in long-term care"--Provided by publisher.